2004
DOI: 10.1023/b:joor.0000018329.79751.09
|View full text |Cite
|
Sign up to set email alerts
|

The Worker Role Interview—Preliminary Data on the Predictive Validity of Return to Work of Clients After an Insurance Medicine Investigation

Abstract: The aim was to investigate the predictive validity of the Worker Role Interview (WRI) for return to work at a two-year follow up of clients who attended an insurance medicine investigation centre. The WRI identifies psychosocial and environmental factors, that influence a person's abilities to return to work. Forty-eight of 202 consecutively selected clients constituted the study group. The Mann-Whitney U test was used to test the statistically significant differences in WRI ratings between those who were work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 3 publications
(2 reference statements)
1
28
0
Order By: Relevance
“…In general, there is a lack of such methods, and this applies also within the area of physiotherapy. Occupational therapists have developed different types of work ability assessment methods (Ekbladh, Haglund, and Thorell, 2004;Sandqvist, 2007) based on the Model of Human Occupation (Kielhofner, 2002). These methods can also be used by other health care professionals, such as PTs.…”
Section: Professional Prerequisites For Pt Engagement In Work Abilitymentioning
confidence: 99%
“…In general, there is a lack of such methods, and this applies also within the area of physiotherapy. Occupational therapists have developed different types of work ability assessment methods (Ekbladh, Haglund, and Thorell, 2004;Sandqvist, 2007) based on the Model of Human Occupation (Kielhofner, 2002). These methods can also be used by other health care professionals, such as PTs.…”
Section: Professional Prerequisites For Pt Engagement In Work Abilitymentioning
confidence: 99%
“…A Swedish study reported that five of the 17 WRI items have ''tentative'' predictive validity for return to work (29). This study followed a group of clients who attended an insurance medicine investigation center.…”
Section: The Worker Role Interviewmentioning
confidence: 99%
“…However, results showed that diagnosis and treatment were much stronger predictors of return-to-work than cancer-related symptoms such as fatigue, depressive symptoms or cognitive problems. In addition, recent empirical studies have indicated the importance of patients' expectations of recovery as good predictors of return-to-work and rehabilitation independent of diagnosis and treatment (Ekbladh et al, 2004;. Studies in other disorders have also shown that a patient's own assessment of work ability (Reiso et al, 2003), expectation of job success (Ekbladh et al, 2004) and work recovery expectations (Hogg-Johnson and Cole, 2003;Nieuwenhuijsen et al, 2006;Turner et al, 2006) do predict return-to-work.…”
mentioning
confidence: 99%